Phosphatidylserine-Liposomes Promote Tolerogenic Features on Dendritic Cells in Human Type 1 Diabetes by Apoptotic Mimicry - Rodriguez-Fernandez, Silvia; Pujol-Autonell, Irma; Brianso, Ferran; Perna-Barrull, David; Cano-Sarabia, Mary; Garcia-Jimeno, Sonia; Villalba, Adrian; Sanchez, Alex; Aguilera, Eva; Vazquez, Federico; Verdaguer, Joan; Maspoch, Daniel; et al. (Frontiers in Immunology, 2018)
Type 1 diabetes (T1D) is a metabolic disease caused by the autoimmune destruction of insulin-producing β-cells. With its incidence increasing worldwide, to find a safe approach to permanently cease autoimmunity and allow β-cell recovery has become vital. Relying on the inherent ability of apoptotic cells to induce immunological tolerance, we demonstrated that liposomes mimicking apoptotic β-cells arrested autoimmunity to β-cells and prevented experimental T1D through tolerogenic dendritic cell (DC) generation. These liposomes contained phosphatidylserine (PS) —the main signal of the apoptotic cell membrane— and β-cell autoantigens. To move towards a clinical application, PS-liposomes with optimum size and composition for phagocytosis were loaded with human insulin peptides and tested on DCs from patients with T1D and control age-related subjects. PS accelerated phagocytosis of liposomes with a dynamic typical of apoptotic cell clearance, preserving DCs viability. After PS-liposomes phagocytosis, the expression pattern of molecules involved in efferocytosis, antigen presentation, immunoregulation and activation in DCs concurred with a tolerogenic functionality, both in patients and control subjects. Furthermore, DCs exposed to PS-liposomes displayed decreased ability to stimulate autologous T cell proliferation. Moreover, transcriptional changes in DCs from patients with T1D after PS-liposomes phagocytosis pointed to an immunoregulatory prolife. Bioinformatics analysis showed 233 differentially expressed genes. Genes involved in antigen presentation were downregulated whereas genes pertaining to tolerogenic/anti-inflammatory pathways were mostly upregulated. In conclusion, PS-liposomes phagocytosis mimics efferocytosis and leads to phenotypic and functional changes in human DCs, which are accountable for tolerance induction. The herein reported results reinforce the potential of this novel immunotherapy to re-establish immunological tolerance, opening the door to new therapeutic approaches in the field of autoimmunity.